Empirical Analysis of Runtime Distributions of Neighbourhood Search for the Graph Coloring Problem — Code and Data - Peeraya Thapatsuwan; Warattapop Thapatsuwan; Chaichana Kulworatit (Zenodo (CERN European Organization for Nuclear Research), 2026)
Code and experimental data accompanying the paper "Empirical Analysis of Runtime Distributions of Neighbourhood Search for the Graph Coloring Problem." Contains Python and C implementations of four neighbourhood search algorithms (Random Walk, TABUCOL, PARTIALCOL, Ising heuristic), experiment runners, raw result data (300 trials × 4 algorithms × 27 planted-partition instances + 14 DIMACS-equivalent instances), and figure generation scripts.